The effect of digital rectal exam on the 4Kscore for aggressive prostate cancer. Issue 7 (19th February 2018) - Maccini, Michael A.; Westfall, Nicholas J.; Van Bokhoven, Adrie; Lucia, Marshall Scott; Poage, Wendy; Maroni, Paul D.; Wilson, Shandra S.; Glodé, Leonard Michael; Arangua, Paul; Newmark, Jay; Steiner, Mitchell; Werahera, Priya N.; et al.
Abstract : Background: The 4Kscore is a new commercially available blood‐based diagnostic test which predicts risk for aggressive, clinically significant prostate cancer on prostate biopsy. The 4Kscore is currently restricted to patients who have not had a digital rectal exam (DRE) in the previous 96 h, owing to prior mixed data suggesting that prostate specific antigen (PSA) isoforms may increase by a statistically significant—if not necessarily clinically significant—amount shortly after DRE. Our primary objective was to determine if 4Kscore test results are affected by a preceding DRE. Methods: Participants at a Prostate Cancer Awareness Week screening event sponsored by the Prostate Conditions Education Council filled out clinical history questionnaires and had blood samples for 4Kscore testing drawn prior to DRE, then 15‐45 min following DRE. Patients with prior cancer diagnosis, 5‐alpha reductase inhibitor medication use, or lower urinary tract procedures in the prior 6 months were excluded, resulting in a population of 162 participants for analysis. Values were then compared to determine if there was a significant difference in 4Kscore following DRE. Results: A statistically significant increase was seen in levels of 3 kallikreins measured (total PSA, free PSA, and intact PSA; median <0.03 ng/mL for all). This resulted in a small but statistically significant decrease in post‐DRE 4Kscore (median absolute score decrease 0.43%). Using a 4Kscore cutoff of 7.5% resulted in reclassification of 10 patients (6.2%), nine of whom were "downgraded" from above the cutoff to below. Conclusions: If the blood draw for the 4 K score is performed after a screening DRE, there is a statistically significant difference in the 4 K score results, but in the vast majority of cases it would not affect clinical decision making.